Senescent renal tubular epithelial cells activate fibroblasts by secreting Shh to promote the progression of diabetic kidney disease - Wang, Dan; Yin, Ling; Chen, Rongyu; Tan, Wanlin; Liang, Luqun; Xiang, Jiayi; Zhang, Huifang; Zhou, Xingcheng; Deng, Huaqing; Guo, Bing; Wang, Yuanyuan (Frontiers in Medicine, 2023)
Diabetic kidney disease (DKD) is one of the complications of diabetes; however, the pathogenesis is not yet clear. A recent study has shown that senescence is associated with the course of DKD. In the present study, we explored whether senescent renal tubular cells promote renal tubulointerstitial fibrosis by secreting Sonic hedgehog (Shh) which mediates fibroblast activation and proliferation in DKD. A 36-week-old db/db mice model and the renal tubular epithelial cells were cultured in high glucose (HG, 60 mmol/L) medium for in vivo and in vitro experiments. Compared to db/m mice, blood glucose, microalbuminuria, serum creatinine, urea nitrogen, and UACR (microalbuminuria/urine creatinine) were markedly increased in db/db mice. Collagen III, monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor-alpha (TNF-α) were also increased in db/db mice kidneys, suggesting fibrosis and inflammation in the organ. Moreover, the activity of SA-β-Gal in the cytoplasm of renal tubular epithelial cells increased, and the cell cycle inhibition of the expression of senescence-related gene cell cycle inhibitor p16INK4A protein and p21 protein increased, indicating that renal fibrosis in db / db mice was accompanied by cell senescence. Furthermore, Shh is highly expressed in the injured renal tubules and in the kidney tissue of db/db mice, as detected by ELISA. The results of immunofluorescence staining showed increased positive staining for Shh in renal tubular epithelial cells of db/db mice and decreased positive staining for Lamin B1, but increased positive staining for γH2A.X in cells with high Shh expression; similar results were obtained in vitro. In addition, HG stimulated renal tubular epithelial cells to secrete Shh in the supernatant of the medium. D-Gal treatment of renal tubular epithelial cells increased the protein levels of Shh and p21. We also found enhanced activation and proliferation of fibroblasts cultured with the supernatant of renal tubular epithelial cells stimulated by HG medium but the proliferative effect was significantly diminished when co-cultured with cyclopamine (CPN), an inhibitor of the Shh pathway. In conclusion, HG induces renal tubular epithelial cell senescence, and the secretion of senescence-associated proteins and Shh mediates inflammatory responses and fibroblast activation and proliferation, ultimately leading to renal fibrosis.